Continuous variables for single photons - Zhang, L; Mukamel, E; Walmsley, I; Silberhorn, C; U'Ren, AB; Banaszek, K (2007)
Photons have a rich structure associated with their continuous degrees of freedom, the transverse wavevector and frequency. This modal structure can play an important role in quantum information processing based on photons. In particular, information may be coded into any of the degrees of freedom, and this means that photons may represent not only qubits, but also qudits, or qunats - where the continuous degrees of freedom are involved. Coding into quantum correlations in these degrees may be usefully employed to transmit more than one bit per photon in a secure communications link. However, it may also be detrimental: for example, it can hinder the preparation of pure states via conditional detection, and thus compromise the efficacy of quantum information processing schemes based on interference. We illustrate some general criteria that are useful for source design for QIP.